Child abuse and its mimics in skin and bone - Brogdon, B. G. (Byron Gilliam); Shwayder, Tor.; Elifritz, Jamie (Boca Raton : CRC Press/Taylor & Francis, 2013)
"Of all children reported to child protective services for suspected maltreatment in any form, the percentage of substantiated cases of physical abuse actually is quite small. There are a number of dermatological and radiologically demonstrable musculoskeletal lesions that have been, or could be mistaken for, intentional physical abuse by the inexperienced or under-educated observer. This atlas illustrates the classic manifestations of physical abuse by dermatological and radiological examination as a standard against which the mimickers of physical abuse can be compared. Where appropriate, the authors provide pertinent historical, physical and laboratory information in support of the diagnosis"--Provided by publisher.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Forensic radiography; Musculoskeletal system; Electronic books